MALAYSIA STROKE CONFERENCE 2022 1: E-Poster Presentation - 2022, Malaysia Stroke Conference (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
1. A REVIEW ON THE IMPACT OF ENDOGENOUS AND EXOGENOUS TESTOSTERONE ON ACUTE ISCHEMIC STROKE IN MEN 2. CASE REPORT OF SUCCESSFUL THROMBOLYSIS IN YOUNG ADULT WITH ACUTE ISCHAEMIC STROKE SECONDARY TO HOMOCYSTEINEMIA 3. SPONTANEOUS CORONARY ARTERY DISSECTION AND POSTERIOR REVERSIBLE ENCEPHALOPATHY SYNDROME- A RARE STROKE MIMIC 4. DRIVING RISK AMONGST STROKE PATIENTS: A NOVEL DRIVING SCREENING TOOL 5. THE TREND OF ONSET-TO-DOOR TIME AMONG ISCHEMIC STROKE PATIENTS IN SEBERANG JAYA HOSPITAL IN RELATIONSHIP TO THE NATIONAL NUMBER OF COVID-19 CASES 6. THE TREND OF DOOR-TO-NEEDLE TIME AMONG ISCHEMIC STROKE PATIENTS IN SEBERANG JAYA HOSPITAL IN RELATIONSHIP TO THE NUMBER OF COVID-19 CASES 7. THE ASSOCIATION OF BODY MASS INDEX AND STROKE SEVERITY, STROKE TYPE AND STROKE SUBTYPE 8. ASSOCIATION OF ADMISSION BLOOD PRESSURE WITH STROKE SEVERITY AND FUNCTIONAL OUTCOME IN ACUTE ISCHEMIC STROKE PATIENTS WHO RECEIVED INTRAVENOUS THROMBOLYSIS IN SEBERANG JAYA HOSPITAL 9. ASSOCIATION OF STROKE SEVERITY WITH HOSPITAL DISTANCE, ECONOMIC STATUS AND HOSPITAL ARRIVAL TIME AMONG STROKE PATIENTS IN HOSPITAL SEBERANG JAYA